A What Works Centre for Probation: Challenges and possibilities. (March 2022) - Sanders, Michael; Jones, Louise; Briggs, Eleanor
The What Works Movement in the UK Government has seen the establishment of 12 centres to focus on evidence-based policy in different domains. In this paper, we present the challenges and opportunities posed by a What Works Centre (WWC) for Probation, based on our prior experience of establishing WWCs in other areas. Although there are legitimate and substantial challenges to some of the methodological approaches of 'What Works', we conclude that Probation is in an unusually strong starting position for such a centre to thrive.